Effectiveness of Smartphone App for the Treatment of Pediatric Obesity: A Randomized Controlled Trial - Giuseppina Rosaria Umano; Mariapia Masino; Grazia Cirillo; Giulia Rondinelli; Francesca Massa; Giuseppe Salvatore R. C. Mangoni di Santo Stefano; Anna Di Sessa; Pierluigi Marzuillo; Emanuele Miraglia del Giudice; Pietro Buono (MDPI AG, 2024)
Background: Pediatric obesity treatment is based on high-intensity lifestyle counseling. However, high dropout rates and low effectiveness have been reported, even in specialized centers. Mobile health technologies have been used to overcome these limits with contrasting results. This study aims at evaluating the effectiveness of a six-month intervention with a mobile app for the treatment of pediatric obesity at 6 and 12 months of follow-up. Methods: Seventy-five patients were randomly assigned to standard care or standard care plus mobile app (2:1) using an online randomizer system. The mobile app delivered high-intensity lifestyle counseling for diet and physical activity. Results: At six months of follow-up, the M-App group showed significantly lower dropout rates compared to standard care (p = 0.01). The risk of dropout was significantly higher in controls compared to the intervention group (OR 3.86, 95% C.I. 1.39-10.42, p = 0.01). After one year, we observed lower albeit non-statistically significant dropout rates in the M-App compared to the standard care group (p = 0.24). No differences were observed in z-score BMI and percentage of BMI reduction between the two groups. Conclusions: Our findings suggest that the mobile app might help in the clinical management of children and adolescents with obesity in terms of dropout reduction.